Inovasi Pedagogis melalui pelatihan penulisan bahan ajar Bahasa Inggris berbasis Cross Cultural Understanding - Arsyad, Safnil; Syahrial, Syahrial; Monica, Shella (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Teaching materials based on Cross Cultural Understanding (CCU) are educational resources that provide information on cross-cultural understanding, presenting reading texts complemented with questions and learning activities focused on the cultural contrasts between Indonesia and foreign countries. The innovation of teaching materials for pedagogical purposes is crucial in the learning process. Hence, this activity aims to assist high school English teachers in Lubuklinggau through a Cross Cultural Understanding approach, enabling them to develop effective teaching materials. This initiative highlights the importance of cultural understanding in English language teaching, with an emphasis on contrasting local and target cultures. Involving 40 teachers from 23 schools, the training included presentations on cultural integration, the CCU concept, examples of CCU-based teaching materials, and the creation of questions oriented towards High Order Thinking Skills (HOTS). The results indicate that the training significantly enhanced the teachers' understanding and skills in integrating cultural aspects into English language teaching materials, as well as their awareness of the importance of cross-cultural sensitivity. This is reflected in the high satisfaction rates, with 87.5% of the participants affirming that the training content met their needs and 90% feeling they had directly benefited. This study underscores the significance of CCU training in professional development for teachers and highlights the necessity for more inclusive and culturally sensitive educational approaches in both global and local contexts